HUBUNGAN PERAN TENAGA PROMOSI KESEHATAN PADA GERMAS DENGAN PENCEGAHAN PENYAKIT TIDAK MENULAR DI PUSKESMAS AEK PAROMBUNAN KOTA SIBOLGA TAHUN 2020 - Simaremare, Harapan Maruli Tua (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2021)
Non Communicable Diseases (NCD) is one of the main causes of death in the word as well as in the working area of Puskesmas Aek Parombunan in Sibolga. The aim of this study was to find out the relationship between health promotions workers in Community Movement with the prevention of Non Communicable Disease in Puskesmas Aek Parombunan. The research is quantitative research by using cross sectional analysis research design. The sample was 96 patient who came for treatment at Puskesmas Aek Parombunan in 2020. The resulth of the research showed that there was a relationship betwen the role of health promotion workers in Community Movement with the prevention of non communicable disease. It can be concludedthat there is a significant relationship between the role of health promotion personnel in germas as counselors and prevention of non communicable diseases with a coefficient value of 5,751. The results showed that there was a relationship between the role oh health promotion personnel in germas and the prevention of non communicable diseases at the Aek Parombunan Public Health Center in Sibolga City in 2020 as evidenced by the results of statistical test using the chi square test,it was found that there was a significant relationship 5% obtained p-value=0,000<0,005. Knowledge and experience of health promotion personnel are needed in carrying out their function as health promotors in socciety who are very influental in order to change people’s behavior to carry out a healthy lifestyle community movement to prevent non communicable diseases